Aligning Maqasid al-Shariah and Sustainable Development Goals: A Multidimensional Welfare Analysis from South Sumatra, Indonesia - Kamalia Sani; Puspa Utami (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the alignment between Maqasid al-Shariah and the Sustainable Development Goals (SDGs) through a multidimensional welfare framework in South Sumatra, Indonesia during the 2020–2025 period. The study develops a sub-national Maqasid-based Welfare Index (MWI) by incorporating five dimensions: social welfare (Din), health (Nafs), education (Aql), human development (Nasl), and economic welfare (Mal), proxied respectively by social indicators, life expectancy, mean years of schooling, Human Development Index (HDI), and poverty rate. Using panel data across districts/cities, this research applies a composite index approach combined with panel regression analysis to examine the determinants and dynamics of multidimensional welfare. The results reveal a significant welfare decline during the COVID-19 pandemic in 2021, followed by a gradual recovery throughout 2022–2025. The regression findings indicate that health and education exert positive and significant effects on Maqasid-based welfare, while poverty negatively affects welfare performance. The findings demonstrate that the integration of Maqasid al-Shariah and SDGs provides a broader welfare perspective beyond conventional economic indicators. Despite improvements in human development, regional disparities and poverty remain major challenges for inclusive welfare achievement. This study contributes empirically by operationalizing a Maqasid-based Welfare Index (MWI) at the sub-national level and offers policy implications for strengthening human capital investment, social protection, and sustainable regional development strategies in Indonesia.